Evaluation of leptospirosis knowledge, attitude and practice among dog handlers - Goh, Soon Heng; Khor, Kuan Hua; Lau, Seng Fong; Ismail, Rosnah; Bejo, Siti Khairani; Radzi, Rozanaliza (Veterinary Association Malaysia, 2019)
Dogs could be reservoirs and carriers of Leptospira spp., hence, may play a potential role in disease transmission, exposing dog handlers to leptospirosis. This study evaluated the dog handlers’ knowledge, attitude and practice (KAP) towards leptospirosis. Four working dog and four dog shelter organisations were approached. A total of 138 dog handlers were conveniently recruited and evaluated on their level of knowledge, attitude and practice towards leptospirosis using a validated structured questionnaire. Most of the dog handlers were male aged between 30 and 40 years with a wide range of working experience of 1 - 10 years and all of them have no formal training about leptospirosis. The majority of the dog handlers from the dog shelters had poor knowledge (90%, n=34/38) and attitude (100%, n=38/38) and moderate practice (53%, n=20/38) towards leptospirosis, whereas the working dog handlers had poor knowledge (58%, n=58/100) and attitude (75%, n=75/100) but a good level of practice (77%, n=77/100). The poor attitude towards leptospirosis in both groups is alarming as it may hinder implementation plans of control and preventive measures. Although there was good hand-washing practices among the dog handlers, there was a lack of personal protective equipment (PPE) practice that may therefore expose both the dogs and dog handlers to leptospirosis. Information gained from this study could be used to implement intervention programmes and to suggest prevention measures to limit the risk of leptospirosis among the dog handlers.